Roles of NOD1 (NLRC1) and NOD2 (NLRC2) in innate immunity and inflammatory diseases. Issue 6 (15th October 2012) - Correa, Ricardo G.; Milutinovic, Snezana; Reed, John C.
Abstract : NOD1 {nucleotide-binding oligomerization domain 1; NLRC [NOD-LRR (leucine-rich repeat) family with CARD (caspase recruitment domain) 1]} and NOD2 (NLRC2) are among the most prominent members of the NLR (NOD-LRR) family –proteins that contain nucleotide-binding NACHT domains and receptor-like LRR domains. With over 20 members identified in humans, NLRs represent important components of the mammalian innate immune system, serving as intracellular receptors for pathogens and for endogenous molecules elaborated by tissue injury. NOD1 and NOD2 proteins operate as microbial sensors through the recognition of specific PG (peptidoglycan) constituents of bacteria. Upon activation, these NLR family members initiate signal transduction mechanisms that include stimulation of NF-κB (nuclear factor-κB), stress kinases, IRFs (interferon regulatory factors) and autophagy. Hereditary polymorphisms in the genes encoding NOD1 and NOD2 have been associated with an increasing number of chronic inflammatory diseases. In fact, potential roles for NOD1 and NOD2 in inflammatory disorders have been revealed by investigations using a series of animal models. In the present review, we describe recent experimental findings associating NOD1 and NOD2 with various autoimmune and chronic inflammatory disorders, and we discuss prospects for development of novel therapeutics targeting these NLR family proteins.